Potensi Tepung Jewawut dalam Meningkatkan Kadar Fe dan Daya Terima Nugget Ayam - Yuwono Setiadi; Sunarto Sunarto; Sihol P. Hutagalung (Poltekkes Kemenkes Semarang, 2015)
This research aimed to determine Fe content of chicken nuggets which substituted with barley flour and its acceptability. The research was conducted three phases, namely: production of barley flour; production of chicken nuggets and perform iron assay and the acceptability test of chicken nuggets on pregnant women. In this research, chicken nuggets is produced with barley flour substitution of 0%, 10%, 20%, 30% and 40%. The research design is pure experimental with completely randomized design 1 (one) factor, namely the concentration of substitution and 5(five) levels of treatment, namely: 0%, 10%, 20%, 30% and 40%. The number of repeat was 2 (two) times. The measured variables were iron content and acceptability. Data analysis was performed using ANOVA (Analysis of Variance) and ANOVA Repeated Measure. Barley flour substitution on chicken nuggets cause an increase in iron content (13.86 ppm to 16.90 ppm; 17.48 ppm; 18.34 ppm; 18.98 ppm). The most preferred nuggets is chicken nugget with 10% substitution of barley flour. It concluded that substitution of barley flour into chicken nuggets increasing Fe content, the most preferred nugget is chicken nuggets with 10% substitution of barley flour. The soaking and heating treatment were needed on barley grains in order to avoid unpleasant aroma on nuggets.